Chapter 3 So-Called Social Justice Teaching and Multicultural Teacher Education: Rhetoric and Realities - Haddix, Marcelle M. (Taylor & Francis, 2017)
Cultivating Racial and Linguistic Diversity in Literacy Teacher Education examines how English and literacy teacher education-a space dominated by White, English-monolingual, middle class perspectives-shapes the experiences of preservice teachers of color and their construction of a teacher identity. Significant and timely, this book focuses attention on the unique needs and perspectives of racially and linguistically diverse preservice teachers in the field of literacy and English education and offers ways to improve teacher training to better meet the needs of preservice teachers from all racial, ethnic, and linguistic backgrounds. These changes have the potential to diversify the teacher force and cultivate teachers who bring rich racial, cultural, and linguistic histories to the field of teaching.